Barrier mechanisms in the developing brain: mechanisms and misunderstandings - Saunders, Norman (Henry Stewart Talks, 2009)
The brain barriers, Historical perspective, Morphology of cerebral blood vessels and choroid plexus in the development brain, Are tight junctions functionally tight?, Ion and water transfer mechanisms, Origin and significance of high CSF protein concentration in embryos, CSF-brain barrier in the developing brain
Archived at 2018/05/31